2021
DOI: 10.3390/ph14121243
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of SARS-CoV-2 Nsp14 and Nsp16 Methyltransferase Inhibitors by High-Throughput Virtual Screening

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) uses mRNA capping to evade the human immune system. The cap formation is performed by the SARS-CoV-2 mRNA cap methyltransferases (MTases) nsp14 and nsp16, which are emerging targets for the development of broad-spectrum antiviral agents. Here, we report results from high-throughput virtual screening against these two enzymes. The docking of seven million commercially available drug-like compounds and S-adenosylmethionine (SAM) co-substrate analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Several studies have searched for small molecules that can inhibit MTase activity. Bobrovs et al computationally screened the docking of 7 million compounds with nsp14 and nsp16 and found 80 candidates, 39 for nsp14 and 41 for nsp16 [ 6 ]. They experimentally assayed them and found 9 that displayed MTase inhibition with an IC 50 < 200 μM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have searched for small molecules that can inhibit MTase activity. Bobrovs et al computationally screened the docking of 7 million compounds with nsp14 and nsp16 and found 80 candidates, 39 for nsp14 and 41 for nsp16 [ 6 ]. They experimentally assayed them and found 9 that displayed MTase inhibition with an IC 50 < 200 μM.…”
Section: Discussionmentioning
confidence: 99%
“…There have been numerous efforts to find ways to disrupt SARS-CoV-2 MT activity using small molecules [ [6] , [7] , [8] , [9] ]. Other SARS-CoV studies have shown that synthetic peptides can interfere in the binding of nsp10 to nsp14 or to nsp16 and can diminish or modulate viral replication [ [10] , [11] , [12] , [13] , [14] ].…”
Section: Introductionmentioning
confidence: 99%
“…However, very few compounds have been identified as potential inhibitors of SARS-CoV-2. 14 18 In addition to the drug-repurposing approach, the method of de novo drug discovery with structure-guided design of nsp14 substrates yielded potent inhibitors with IC 50 values in the nanomolar to submicromolar range. 19 , 20 However, both articles did not report studies on the inhibitory activity of these nsp14 inhibitors in SARS-CoV-2-infected cells.…”
Section: Introductionmentioning
confidence: 99%
“… 21 , 22 In addition, virtual screenings have been performed to identify potential Nsp14 MTase inhibitors. 23 However, most of these inhibitors are highly polar and no anti-SARS-CoV-2 activity has been reported. During the preparation of this manuscript, potent and selective bisubstrate inhibitors that contained an sulfonamide functionality were reported; however, no antiviral activity was disclosed.…”
mentioning
confidence: 99%